Case Report: Pathological Complete Response to Neoadjuvant Alectinib in a Patient With Resectable ALK-Positive Non-Small Cell Lung Cancer - Hu, Yan; Ren, Siying; Wang, Ruoyao; Han, Wei; Xiao, Peng; Wang, Li; Yu, Fenglei; Liu, Wenliang (Frontiers in Pharmacology, 2022)
Background: Alectinib, a highly selective inhibitor of ALK, is currently used in the first-line setting of untreated advanced ALK-positive NSCLC and in the second-line setting of crizotinib-resistant ALK-positive NSCLC. Despite promising efficacy and tolerability in the treatment of advanced ALK-positive NSCLC, the activity of alectinib as neoadjuvant therapy in resectable ALK-positive NSCLC remains to be investigated. Case presentation: Herein, we report a case of a 58-year-old female patient presented to our hospital with hemoptysis for 1 month. Contrast-enhanced computerized tomography (CT) of the chest showed an approximately 4.2 × 3.4 cm mass in the right hilum with localized obstructive pneumonia in the right lower lobe and multiple enlarged lymph nodes in the right hilum and mediastinum. Serum oncological markers results showed elevated levels of CA19-9, CEA, CA125, and CA242. Bronchoscopic biopsy of the mass showed poorly differentiated pulmonary adenocarcinoma and immunohistochemical testing results confirmed ALK positivity. Neoadjuvant alectinib was given at a dosage of 600 mg twice per day for two cycles (56 days), achieving a partial response of the disease with 90% shrinkage of the mass at the subsequent whole-body positron emission tomography. Repeat serum oncological markers results showed that only CA125 was elevated, but lower than before therapy. A bilobectomy of the right middle and lower lobes and systemic lymphadectomy under video-assisted thoracoscopic approach was successfully performed 7 days after the last dose of alectinib. Postoperative pathology showed pathological complete response (pCR). The patient experienced an uneventful postoperative course and continued to receive alectinib and did not report any specific discomfort at her 8-month follow-up. Thoracoabdominal CT at 8 months postoperatively showed no recurrence and repeated examination of serum oncological markers were negative. Conclusion: We report a case of resectable ALK-positive NSCLC treated with neoadjuvant aletinib achieving pCR. Our case highlights the feasibility of alectinib as neoadjuvant therapy for the treatment of resectable ALK-positive NSCLC. Undoubtedly, the safety and efficacy of this novel treatment modality needs to be explored in future large clinical trials.